Family conference in palliative care: concept analysis - Rudval Souza da Silva; Géssica Sodré Sampaio Trindade; Gilvânia Patrícia do Nascimento Paixão; Maria Júlia Paes da Silva
ABSTRACT Objective: to analyze the attributes, antecedents and consequents of the family conference concept. Method: Walker and Avante's method for concept analysis and the stages of the integrative review process, with a selection of publications in the PubMed, Cinahl and Lilacs databases focusing on the family conference theme in the context of palliative care. Results: the most cited antecedents were the presence of doubts and the need to define a care plan. Family reunion and working instrument were evidenced as attributes. With respect to consequents, to promote the effective communication and to establish a plan of consensual action were the most remarkable elements. Final considerations: the scarcity of publications on the subject was observed, as well as and the limitation of the empirical studies to the space of intensive therapy. Thus, by analyzing the attributes, antecedents and consequents of the concept it was possible to follow their evolution and to show their efficacy and effectiveness as a therapeutic intervention.